A Computer-Based Early Intervention for Thai Preschool Children at Risk of Dyslexia: A Pre- and Postintervention Study - Wannapaschaiyong, Prakasit; Vajrabhaya, Prakaiwan; Rojmahamongkol, Pat; Sutchritpongsa, Sureelak (Journal of Child Science, 2023)
Preschool children at risk of dyslexia show inadequate progress in their preliteracy skills; they often perform poorly in the domain of phonological awareness, letter knowledge, and rapid automatized naming. As a result, they tend to fall behind academically, specifically in reading, when they enter primary school. Because time is of the essence, early intervention becomes necessary to provide the best possible preliteracy outcome. To date, there has not been a study that investigates the effectiveness of early intervention in Thai, a language that is typologically and orthographically different from those in previous studies. In this preliminary study, training materials, created with phonological awareness and letter knowledge at the core, were presented via interactive Siriraj Pre-Literacy Enhancement software. In total, 73 typically developing preschoolers, aged 60 to 66 months, were enrolled. Preliteracy skills were measured by Rama Pre-Read (RPR). At-risk children received the 11-week computer-based early intervention training. After the intervention was completed, participants' preliteracy skills were evaluated by RPR (posttest). Sixteen children (21.9%) were at risk of dyslexia. Results after training indicated that preschool at-risk children of dyslexia in Thailand show a high magnitude of improvement in preliteracy skills, across all three domains. The computer-based early intervention to promote preliteracy skills is a feasible and effective form of remediation for Thai children at risk of dyslexia.
Keywords: at-risk children; dyslexia; computer based; early intervention; preliteracy